Protein sumoylation in normal and cancer stem cells - Zhu, Qiuhong; Liang, Panpan; Chu, Cuiying; Zhang, Aili; Zhou, Wenchao (Frontiers in Molecular Biosciences, 2022)
Stem cells with the capacity of self-renewal and differentiation play pivotal roles in normal tissues and malignant tumors. Whereas stem cells are supposed to be genetically identical to their non-stem cell counterparts, cell stemness is deliberately regulated by a dynamic network of molecular mechanisms. Reversible post-translational protein modifications (PTMs) are rapid and reversible non-genetic processes that regulate essentially all physiological and pathological process. Numerous studies have reported the involvement of PTMs in the acquirement and maintenance of cell stemness. Recent studies underscore the importance of protein sumoylation, i.e., the covalent attachment of the small ubiquitin-like modifiers (SUMO), as a critical PTM in the stem cell populations in development and tumorigenesis. In this review, we summarize the functions of protein sumoylation in different kinds of normal and cancer stem cells. In addition, we describe the upstream regulators and the downstream effectors of protein sumoylation associated with cell stemness. We also introduce the translational studies aiming at sumoylation to target stem cells for disease treatment. Finally, we propose future directions for sumoylation studies in stem cells.